2020
DOI: 10.1111/ajco.13423
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study comparing mannitol with furosemide for the prevention of cisplatin‐induced renal toxicity in non‐small cell lung cancer: The OLCSG1406 trial

Abstract: Aim Evidence is lacking on the best standard method for forced diuresis to prevent cisplatin‐induced nephrotoxicity. We compared the cisplatin‐induced nephrotoxicity prevention effect of furosemide or mannitol in patients with advanced non‐small cell lung cancer. Methods Patients with advanced non‐small cell lung cancer suitable to receive cisplatin‐containing regimen were randomly assigned to receive furosemide or mannitol with appropriate hydration. The primary endpoint was the proportion of ≥ grade 1 serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Some of them reported that mannitol has a protective effect on the kidneys by its diuretic mechanism and reducing CP concentration [ 24 , 25 ]. On the contrary, some others studies declared no protective effect for mannitol, or even in confirmation with our study, they found mannitol to be significantly more nephrotoxic [ 16 , 26 , 27 ]. Morgan et al indicated that forced diuresis increased the risk of acute kidney injury due to volume decreasing [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Some of them reported that mannitol has a protective effect on the kidneys by its diuretic mechanism and reducing CP concentration [ 24 , 25 ]. On the contrary, some others studies declared no protective effect for mannitol, or even in confirmation with our study, they found mannitol to be significantly more nephrotoxic [ 16 , 26 , 27 ]. Morgan et al indicated that forced diuresis increased the risk of acute kidney injury due to volume decreasing [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The nephroprotective effect of mannitol and furosemide have also been compared. Santoso et al concluded that furosemide-saline has more nephroprotective effect compared with mannitol [ 16 ], while other studies considered no significant difference in their protective role [ 26 ]. However, in our study, no significant protective effect was observed for furosemide-saline hydration in male rats, but the serum levels of BUN and Cr increased significantly when compared with the CP group in female rats.…”
Section: Discussionmentioning
confidence: 99%
“…To better and more comprehensively evaluate the effect of mannitol on cisplatin-induced kidney injury, we divided some articles into different studies without affecting the integrity of the data. Makimoto 2020 ( 50 ) recorded data of patients at first and all courses of treatment, respectively, and it was divided into two studies: Makimoto 2020 (First) for data at first course and Makimoto 2020(Entire) for data over the entire course . Morgan 2014 ( 35 ) integrally recorded data according to the different doses of cisplatin; therefore, we regarded it as two different studies: Morgan 2014 (100 mg) for data at 100 mg/m 2 of cisplatin and Morgan 2014 (30 mg) for data at 30 mg/m 2 of cisplatin .…”
Section: Resultsmentioning
confidence: 99%
“…Two subgroups were divided according to the control treatment. Six studies ( 49 , 51 , 54 , 56 , 57 ) were into “saline,” while Makimoto 2020 ( 50 ) [including Makimoto 2020 (entire) and Makimoto 2020 (first)] were into “furosemide.” There was no heterogeneity across the six saline studies ( p = 0.73, I 2 = 0%) and furosemide studies ( p = 0.63, I 2 = 0%). Therefore, a fixed-effects model was used for pooled analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a research by El Hamamsy in (2017) (38) reported that when compared to hydration and acetazolamide, hydration and mannitol exhibits more frequent cisplatin-induced acute kidney injuries. However, Hamroun (39) and Makimoto (40) stated that there's still no compelling evidence of signi cance in the use of mannitol in regards of reducing nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%